The effectiveness of video-based exercise training program for people with intellectual disability: a multicenter study - Kwan, Rachel; Szeto, Grace; Ho, Ester; Wu, Annie; Wong, Lavinia; Ho, Gilbert; Lau, Rufina; Wong, Eyckle; Kwok, Anthony; Cheung, Dorothy (Frontiers in Sports and Active Living, 2024)
Objective To examine the effectiveness of a specially designed video-based exercise program in promoting physical and balance performance in people with intellectual disability. Methods This study was a multicenter controlled trial. Participants with intellectual disability were divided into exercise group and control group by cluster sampling. The participants in the exercise group received 1 h exercise training sessions twice a week for 8 weeks, and the controls continued their usual care without exercise training. The exercises were specially designed to match the physical ability level of the participants classified as high and low, and a third group called “special” was designed for those wheelchair-bound persons with limited mobility. Elements of light-tempo music and animation were introduced in the videos to motivate the participants. Recording the exercises in video format makes it easier for the class instructors and participants to perform the exercises together, and ensure consistency across different exercise groups conducted in different centers. Each participant underwent the pre- and post-intervention assessment including 30-s chair stand repetitions, five-time chair stand duration, 4-m comfortable walk time, standing static balance level, 6-min walk test, and short physical performance battery score. These variables were compared within each group at pre- and post-intervention stages, and they were also compared between the two groups. Results A total of 180 participants were enrolled in 16 subcenters, including 160 participants in the exercise group and 20 participants in the control group. After 8 weeks of exercise training, there were significant improvements in their physical performance including 30-s chair stand repetitions and five-time chair stand duration, 4-m comfortable walk time and also 6-min walk test, within the exercise group (all P < 0.05). Approximately 39% of the participants in the exercise group also showed significant improvement in standing static balance level. No significant differences were found when compared with the control group participants who did not have any regular exercise participation. Conclusion A specially designed video-based exercise program has demonstrated some positive effects on physical and balance performance after 8 weeks of training among adults with intellectual disability.